Makna Penggalangan Dana Untuk Korban Tragedi Kanjuruhan Pada Penggemar BTS (ARMY) di Twitter Melalui Akun @BTS_AHC_IDN - Isti Halimah Rosanti; Yanuar Ilham; Kurniawan Kurniawan; Hanafi Hanafi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The phenomenon of fundraising among fans is currently a new activity carried out by fan groups. Through the Twitter account @BTS_AHC_IDN, ARMY Indonesia raised funds for the Kanjuruhan tragedy, they became one of the initiators of fundraising which was quite busy in discussion. Because the acquisition of funds is quite large in a short time. This study aims to explain the meaning of fundraising for fans. This research method uses a qualitative phenomenological approach, with the aim of gathering information from informants. The informants for this study were three fans who participated in fundraising and one non-fan who also participated in fundraising. Data collection techniques are in-depth interviews, non-participant observation, and literature study. The results of this study indicate that the three informants had previously participated in fundraising. The because of motive is that fans participate because they are inspired by the idol, because of empathy and also because the distribution is transparent. The in order to motive for fans to participate is because they want to continue to imitate their idols, help the community and victims recover soon. For fans, fundraising is interpreted as a form of empathy and humanity, and also a proof that being a fan can also take positive action..